Mechanical properties of sandwich laminates composite on plywood and glass fibers - Hamzah, Khairum; Shamsudin, Syafiq Asraf; Ab Wahab, Norfariza; Sayed Kushairi, Sayed Nordin; Mustafa, Nuzaimah (Asian Research Publishing Network (ARPN), 2022)
The reinforcement of solid wood and wood-based composite materials is not a new idea, but there have been very few studies about reinforcing plywood with glass fiber composite. In this study, woven glass fibers were used on both outer surfaces of plywood sandwich laminates composite with the help of epoxy resin to improve mechanical properties of standard plywood laminated. The vacuum bagging technique was applied to fabricate plywood sandwich laminate composite test samples with three different thicknesses which is 3 mm, 5 mm and 9 mm, and their mechanical properties were analyzed using tensile and surface roughness tests for different cutting speed parameters of laser cut machine. The collected data were analyzed using analysis of variance (ANOVA), and the microscopic investigation was performed to examine the cross-section structure of ruptured surfaces and its failure morphology during cutting process.